Impact of integrated nutrient management on growth and productivity of clusterbean (Cyamopsis tetragonoloba L.) under limited moisture conditions - Naga, Sunder Devi; Yadav, L.R.; Jat, M.L.; Dhaka, M.S.; Jeetarwal, R.L. (Annals of Agricultural Research, 2016)
Impact of integrated nutrient management on growth and productivity of clusterbean (Cyamopsis tetragonoloba L.) under limited moisture conditions Sunder Devi Naga, L.R. Yadav*, M.L. Jat, M.S. Dhaka and R.L. Jeetarwal Department of Agronomy, S.K.N. College of Agriculture, Jobner, Jaipur, Rajasthan-303 329 E-mail: lalaram69@gmail.com